Analytical BER and PER Performance of Frequency-Domain Diversity Combining, Multipacket Detection and Hybrid Schemes - Ganhão, Francisco (2018)
—Diversity Combining (DC) and Multipacket Detection (MPD) are efficient techniques that cope with packet errors due to severe propagation conditions and/or collisions. To evaluate their network performance on a network simulator, an accurate characterization of the Bit Error Rate (BER) and Packet Error Rate (PER) can successfully replace the behavior of the PHY layer. This choice is better in terms of computational time than implementing a full PHY layer to be jointly simulated with the upper layers. In this paper, an analytical model is proposed to compute the BER and PER of DC, MPD and hybrid techniques, considering a Single-Carrier with Frequency-Domain Equalization (SC-FDE) scenario. The paper also considers two frequency-domain detection methods: a simple linear receiver and a powerful iterative receiver. The proposed model is simple and versatile, since it can support nonhomogeneous transmitting powers, and different channel conditions concerning retransmissions and channel randomization techniques. Several simulations show that the proposed model provides accurate BER and PER results for a wide range of scenarios.